The Impact of Transformation Leadership on Improving Quality Health Service in a Health Center Laban in Riyadh Region - Ayed, Alharbi, Abdullah (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2022)
The quality of health services is one of the basic areas in all services provided by hospitals and health centers, and health institutions need distinguished leaders who can take responsibility to achieve their goals: efficiency and high quality. The presence of conscious administrative leadership that can make optimal use of its resources. This paper aimed to determine the impact of transformational leadership on healthcare quality in Laban Health Center in Riyadh. The result found that among the participants, the most influential results from the Dimensional Transformation Leadership Survey (inspirational motivation) were that 91.6% of respondents believed that their immediate superior makes them feel important in the work they do, the most influential results from the dimension on the quality of healthcare are Survey (Empathy) No. (17), 97% of respondents believe that the nursing staff behaves kindly with accompanying patients. The study aimed to assess the impact of transformational leadership on healthcare quality in Laban Health Center in Riyadh. The study found that the average (dimension of transformational leadership) is (3.95), which is considered a "high level", and this means that the respondents agree that the dimensions of transformational leadership are very high. A mean (dimensions of healthcare) (4.60) is considered ’high’, meaning that participants agree.